Retraction policies of high-impact biomedical journals - Atlas, Michel C. (Medical Library Association, 2004)
Purpose: The purpose is to review the issue of retraction in the scientific literature and to examine the policies on retraction of major biomedical journals. Method: The historical background of this issue was investigated through a literature search. The Instructions to Authors of 122 major biomedical journals were reviewed for evidence of a policy on the retraction of articles. Editors of those journals with no mention of retraction in their Instructions to Authors were contacted by email and/or postal mail. Results: Sixty-two percent of the journals investigated did not post or report having a policy on issuing retractions. Only twenty-one (18%) did. The remainder did not post any policy and did not respond to inquiries. Discussion: Including policies in Instructions to Authors relating to the principled conduct of research and publication will improve the ethical environment in which the scientific community works.